Broadening Our Understanding of “International Academic Staff”: Nationality as a New Marker of Diversity - Marini, Giulio (International Higher Education, 2022)
International academic staff in higher education are considered per se a signal of attractiveness and success. In this article, we discuss the findings of a recent study on international staff working in the United Kingdom. International staff are now fully immersed in all academic functions in their institutions and involved in wider organizational constraints, which raises the issue of their adaptation. Nationality appears to be an important and different marker of diversity.